Strategi Penambahan dan Penghilangan Makna: Kasus Penerjemahan Teks Hukum Bisnis dari Bahasa Inggris ke Bahasa Indonesia - Kotambunan, Florence E (Paradigma: Jurnal Kajian Budaya, 2017)
To show how important the equivalence of ST and TT in business law text is the main goal of this research. Besides that, the benefit of this research is to motivate a translator to become more critical and accurate in producing more quality translations. The results of research can be utilized as a benchmark to conduct further research in a similar study. The library research and field method are commonly administered in translation research. And the technique of analyzing data exerts comparative and causal model between the Source Text (ST) and the Target Text (TT). It is determined that the approach is pursuant to ST and TT both Nord Extra-textual and Intra-textual factors. In addition, the research scope is limited to addition and omission, the strategy of translating in word, phrase or term, clause, and sentence. The conformity of ST and TT to Grice’s maxim is also analyzed as the effect of employing strategy of translating, the addition and omission. These research findings, firstly verifies that extra-textual and intra-textual factors are mostly integrated in achieving equivalence of ST and TT. Secondly, it is also discovered that translation error of deviation, addition, and omission of meaning as the impact of translating strategy application, addition and omission. Thirdly, it is acquired that writing business law text in English is more conventional compared to Indonesian. In conclusion, the translation of business law text complies with faithful and conventional main criteria. Moreover, not only the mastery of other knowledge related but also good collaboration are required between concerned parties and determined the success of translation practice. Therefore, it is wished for these results and implications could be referred to proceed with comprehensive research in other legal texts. Hereafter, it is also advised that proofreading is performed more than twice to minimalize misinterpretation.